Analisis Pemahaman Masyarakat Desa Hedam Kecamatan Heram Kota Jayapura Terhadap Kesadaran Akan Kepedulian Lingkungan - Bernarda Meteray; Kustiyanti Kustiyanti (Jurnal DIKMAS, 2021)
This research aims to analyze the understanding of the community of Hedam Village, Heram Sub-district, Jayapura City, regarding awareness of environmental care. Using qualitative as well as quantitative methods, the research explored data on community attitudes, knowledge, and actions in protecting the environment. The results showed that there is varying awareness among the community, as well as factors that influence environmental awareness. This research is expected to provide recommendations to increase environmental awareness in the community.